OPTIMALISASI STRATEGI BISNIS KOPERASI X DI BUKITTINGGI MELALUI DIGITAL MARKETING DAN PENGELOLAAN KEUANGAN YANG EFEKTIF - Pramadian, Budi; Sari, Laynita; Septiano, Renil (LPPM Universitas Bina Bangsa, 2025)
This study examines the business optimization strategy of Koperasi X in Bukittinggi through the utilization of digital marketing and effective financial management. Based on the Internal-External (IE) Matrix analysis, the cooperative is positioned in the